Projected increases in the annual flood pulse of the western Amazon - Zulkafli,Z; Buytaert,W; Manz,B; Veliz-Rosas,C; Willems,P; Lavado-Casimiro,W; Guyot,JL; Santini,W (Environmental Research Letters, 2016)
The impact of a changing climate on the Amazon basin is a subjectof intensive research because of its rich biodiversity and the significant role ofrainforests in carbon cycling. Climate change has also a direct hydrological impact,and increasing efforts have focused on understanding the hydrological dynamics atcontinental and subregional scales, such as the western Amazon. New projectionsfrom the Coupled Model Inter-comparison Project Phase 5 (CMIP5) ensemble indicateconsistent climatic warming and increasing seasonality of precipitation in the PeruvianAmazon basin. Here we use a distributed land surface model to quantify the potentialimpact of this change in the climate on the hydrological regime of the upper Amazonriver. Using extreme value analysis, historical and future projections of the annualminimum, mean, and maximum river flows are produced for a range of return periodsbetween 1 and 100 years. We show that the RCP 4.5 and 8.5 scenarios of climatechange project an increased severity of the wet season flood pulse (7.5% and 12%increases respectively for the 100-year return floods). These findings agree withpreviously projected increases in high extremes under the Special Report on EmissionsScenarios climate projections, and are important to highlight due to the potentialconsequences on reproductive processes of in-stream species, swamp forest ecology,and socio-economy in the floodplain, amidst a growing literature that more stronglyemphasises future droughts and their impact on the viability of the rainforest systemover greater Amazonia